Cell aggregate and method for producing cell aggregate
By using a molded body of ethylene-vinyl alcohol copolymer fibers to culture adherent cells under stirring, the method achieves larger, viable cell aggregates with improved post-thaw viability, addressing the challenges of uniformity and cryopreservation in cell transplantation therapy.
Patent Information
- Application Number
- JP2023150360
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-15
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2043-09-15
AI Technical Summary
Current methods for producing cell aggregates for cell transplantation therapy face challenges in ensuring uniform cell count and function, and conventional cryopreservation techniques result in low cell viability after thawing.
The method involves carrying adherent cells on a molded body made of fibers containing ethylene-vinyl alcohol copolymers with a nonwoven fiber structure and culturing them under stirring, which results in larger, viable cell aggregates that can withstand freeze-thawing.
This approach produces larger cell aggregates with improved viability during culture and after freeze-thawing, enabling stable cell transplantation effects and reducing the need for frequent cell aggregate preparation.
Smart Images

Figure 2025043058000001 
Figure 2025043058000002 
Figure 2025043058000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a cell aggregate comprising adherent cells and an extracellular matrix, and a method for producing the cell aggregate. [Background technology]
[0002] In recent years, in cell transplantation therapy, in order to fully utilize the functions of transplanted cells, attention has been focused on transplanting cell aggregates (also called cell masses or cell spheroids) created by three-dimensional culture, which more closely reflect the cell-cell interactions and cell-extracellular matrix interactions in the body, rather than single cells cultured in a monolayer.
[0003] Methods for producing cell aggregates have been reported in the past, and representative methods include a method in which cells are cultured using a culture plate with a non-adhesive bottom surface, and cells floating in the medium are allowed to adhere to each other to produce cell aggregates (non-adhesive surface cell culture method), a method in which a cell suspension is dropped onto the inside of a culture plate lid, and the droplets that have become dome-shaped due to surface tension are cultured upside down, so that the cells gather below the droplets due to gravity and adhere to each other to form cell aggregates (hanging drop cell culture method), and a method in which a cell culture chamber is rotated to culture cells, so that the cells come into contact with each other within the chamber to form cell aggregates (rotary cell culture method), etc. Furthermore, a collagen-rich mesenchymal stem cell cell aggregate produced in a growth medium containing a factor that produces collagen, and a frozen graft for mesenchymal stem cell transplantation obtained by freezing and preserving the cell aggregates together with a cryopreservative have been reported (Patent Document 1). [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent No. 7105487 Summary of the Invention [Problem to be solved by the invention]
[0005] In cell transplantation therapy using cell aggregates, it is necessary to prepare cell aggregates for each transplantation operation, but there is no guarantee that the cell number and cell function of the cell aggregates can be uniform. On the other hand, if cell aggregates that meet a certain quality are cryopreserved and then thawed and transplanted at the time of transplantation operation, a stable transplant effect can be expected, but with conventional technology, cell viability after thawing of the cell aggregates is low, making it difficult to cryopreserve the cell aggregates. Therefore, the present invention aims to provide a cell aggregate that can be cryopreserved and a method for producing the cell aggregates. [Means for solving the problem]
[0006] As a result of intensive research, the inventors have surprisingly succeeded in obtaining a cell aggregate by supporting adherent cells on a molded article having a nonwoven fiber structure made of fibers containing an ethylene-vinyl alcohol copolymer and culturing the cells under stirring. Even more surprisingly, it was found that the cell aggregate has a high cell survival rate, with the cells in the center surviving even after freezing and thawing, and can be cryopreserved. Thus, the present invention has been completed.
[0007] That is, the present invention provides the following. (1) A cell aggregate comprising adherent cells and an extracellular matrix, the cell aggregate comprising viable cells even at a depth of 30 μm or more from the surface of the aggregate. (2) A cell aggregate described in (1) above, which contains viable cells even at a depth of 30 μm or more from the surface of the aggregate after freezing and thawing the aggregate. (3) A cell aggregate described in (1) or (2) above, which is granular and has a diameter of more than 1.5 mm. (4) The cell aggregate described in any one of (1) to (3) above, wherein less than 50% of the extracellular matrix is collagen. (5) The cell aggregate according to any one of (1) to (4) above, which is in a frozen state. (6) A method for producing a cell aggregate, comprising supporting adherent cells on a molded body having a nonwoven fiber structure and made of fibers containing an ethylene-vinyl alcohol copolymer, and culturing the cells under stirring. (7) The method according to (6), wherein the fiber containing the ethylene-vinyl alcohol copolymer is a heat-adhesive fiber under moisture. (8) The method according to (6) above, wherein the fiber containing the ethylene-vinyl alcohol copolymer is a conjugate fiber containing a non-thermal adhesive fiber under moisture. (9) The method according to (8) above, wherein the composite fiber is a core-sheath type composite fiber having a sheath portion made of an ethylene-vinyl alcohol copolymer and a core portion made of a polyester resin. (10) The method for producing a cell culture medium according to any one of (6) to (9) above, comprising supporting adherent cells on the molded body having an apparent density of 0.02 to 0.7 g / cm3 and culturing the cells under stirring at 30 to 140 rpm. Effect of the Invention
[0008] According to the present invention, a cell aggregate can be obtained by a simple method in which adherent cells are supported on a molded body having a nonwoven fiber structure made of fibers containing an ethylene-vinyl alcohol copolymer, and the cells are cultured under stirring. The cell aggregate obtained by the present invention is larger in size and has improved cell viability during culture and improved cell viability after freezing and thawing compared to cell aggregates obtained by conventional techniques. The cell aggregate of the present invention is a freezable cell aggregate, since cells in the center of the aggregate survive even after freezing and thawing. Thus, by using the cell aggregate of the present invention, there is no need to prepare a cell aggregate for each treatment, and the lead time of cell transplantation treatment (the time from deciding on treatment to starting treatment) is shortened. [Brief description of the drawings]
[0009] [Figure 1] Micrographs showing the results of a live-dead assay of cell aggregates. [Diagram 2]Micrographs showing the results of a live-dead assay of cell aggregates after freezing and thawing. [Diagram 3] Micrograph showing the results of picrosirius red staining of cell aggregates. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] 1.Cell aggregates As used herein, the term "cell aggregate" refers to a mass of cells formed by the aggregation or aggregation of multiple cells. The cell aggregate of the present invention is an aggregate of adherent cells, and contains extracellular matrix in addition to cells. The cell aggregate of the present invention is a cell aggregate produced outside the body (in vitro or ex vivo).
[0011] In the present specification, the term "adherent cells" refers to cells that grow by adhering to a culture carrier during cell culture. The cells may be derived from any organism, such as animals (e.g., mammals and non-mammals), plants, and insects, and are not particularly limited. Examples of adherent cells include, but are not limited to, osteoblasts, chondrocytes, hematopoietic cells, epithelial cells (e.g., mammary epithelial cells, etc.), endothelial cells (e.g., vascular endothelial cells, etc.), epidermal cells, fibroblasts, mesenchymal cells, cardiac myocytes, myoblasts, smooth muscle cells, skeletal muscle cells derived from living organisms, human tumor cells, fibrocytes, EB virus mutant cells, hepatocytes, kidney cells, bone marrow cells, macrophages, hepatic parenchymal cells, pancreatic β cells, small intestinal cells, mammary cells, salivary gland cells, thyroid cells, skin cells, somatic stem cells (e.g., mesenchymal stem cells, etc.), and the like.
[0012] In the present specification, the term "extracellular matrix" refers to an insoluble substance present outside cells in an organism, and a non-cellular component that fills the gap between cells. The extracellular matrix is mainly composed of water, proteins, and polysaccharides, and is known to have different compositions and forms depending on biological tissues. The extracellular matrix contained in the cell aggregate of the present invention may preferably be an extracellular matrix produced by the adherent cells contained in the cell aggregate themselves. The extracellular matrix contained in the cell aggregate of the present invention contains a relatively small amount of collagen, and for example, less than about 50%, preferably about 48% or less, more preferably about 46% or less of the extracellular matrix is collagen.
[0013] The cell aggregate of the present invention has, for example, a granular shape. The size of the granular cell aggregate may be, for example, a diameter (when not spherical, the longest diameter, hereinafter referred to as "major axis") of about 1.5 mm or more, preferably about 2 mm or more, more preferably about 5 mm or more. The cell aggregate of the present invention may be, for example, a granular aggregate having a major axis of about 1.5 mm to about 5 mm. The diameter of the cell aggregate may be measured by a conventional method, for example, from an image observed under a microscope.
[0014] Furthermore, in the cell aggregates of the prior art, cells in the center of the aggregate die after freezing and thawing, whereas in the cell aggregates of the present invention, cells in the center of the aggregate survive even after freezing and thawing, and cell survival after freezing and thawing is improved compared to the prior art. Also, in the cell aggregates of the prior art, cells in the center of large ones, such as those with a diameter of more than about 1.5 mm, die even without freezing and thawing. In contrast, in the cell aggregates of the present invention, cells in the center survive even in large ones, and cell survival is improved compared to the prior art.
[0015] Here, the central part refers to, for example, a deep part of the cell aggregate that is about 30 μm or more, preferably about 40 μm or more from the surface of the cell aggregate (i.e., an interior of the cell aggregate that is about 30 μm or more, preferably about 40 μm or more away from the surface of the cell aggregate). The distance from the surface of the cell aggregate to the deep part can be measured, for example, by a microscopic image. Furthermore, the survival of cells in the cell aggregate can be confirmed by microscopic observation. Thus, the cell aggregate of the present invention is a freezable cell aggregate, i.e., a cell aggregate that can be frozen and thawed.
[0016] Therefore, the cell aggregate of the present invention may be a cell aggregate in a frozen state. The cell aggregate is preferably frozen in a cryopreservation solution. The cryopreservation solution may be, for example, a cryopreservation solution containing 10% DMSO (Dimethyl sulfoxide), 20% FBS (Fetal Bovine Serum) and 70% DMEM (Dulbecco's Modified Eagle Medium), which is known in the art, or a commercially available cryopreservation solution may be used. Examples of commercially available cryopreservation solutions include, but are not limited to, CELLBANKER1 (manufactured by Xenogen Pharma Co., Ltd.). The cell aggregate may be frozen at a temperature at which freezing is possible, for example, at 0°C or lower, -70°C or lower, or -80°C or lower. The cell aggregate may further be stored in a frozen state, for example, but is not limited to, for 24 hours or more, or even for a long period of time of one month or more. Freezing and cryopreservation may be performed in a freezer or liquid nitrogen. The freezing temperature and the cryopreservation temperature may be the same or different. The freezing temperature may be any temperature at which freezing is possible, and is not particularly limited. The cryopreservation temperature may be any temperature at which the frozen state can be maintained, and is not particularly limited. The freezing temperature, cryopreservation temperature, and storage period may be appropriately selected by those skilled in the art. For example, the cell aggregate may be placed in a freezer at about -70°C to -90°C for about 24 to 72 hours, and then transferred to liquid nitrogen at about -196°C and stored for 24 hours or more.
[0017] The cell aggregate of the present invention is used, for example, as a cell transplant, and is also used in cell-based tests such as screening of anticancer drugs, etc. In particular, since the cell aggregate of the present invention can be frozen and thawed, it can be prepared and stored in advance before use, which is very convenient.
[0018] 2. Preparation of cell aggregates The cell aggregate of the present invention can be produced by a method (hereinafter referred to as "the production method of the present invention") that includes supporting adherent cells on a molded body having a nonwoven fiber structure and made of fibers containing an ethylene-vinyl alcohol copolymer, and culturing the cells under stirring. According to the production method of the present invention, the adherent cells grow in the gaps of the molded body, and the cells gather or aggregate to form cell aggregates, which are then naturally separated from the molded body. Furthermore, the growth and separation are promoted by stirring. That is, the supply of oxygen and nutrients necessary for the survival of the cells to the inside of the nonwoven fiber structure is promoted by stirring, thereby promoting the growth of the cells. Furthermore, the promotion of cell growth leads to the promotion of the formation of cell aggregates by providing the number of cells necessary for the formation of cell aggregates inside the nonwoven fiber structure. Furthermore, the stirring also has the effect of physically separating the cell aggregates formed in the nonwoven fiber structure from the nonwoven fiber structure. Here, the fiber containing an ethylene-vinyl alcohol copolymer is preferably a moist heat adhesive fiber.
[0019] As used herein, the term "nonwoven fiber structure" refers to a board-like structure formed by bonding fibers together rather than weaving them.
[0020] In this specification, the term "heat-and-moisture adhesive fiber" refers to a fiber that contains a heat-and-moisture adhesive resin and can exhibit adhesive function by high-temperature steam or hot water. In this specification, the term "heat-and-moisture adhesive resin" refers to a resin that is softened by high-temperature steam or hot water and can exhibit adhesive function.
[0021] Examples of the heat-and-moisture adhesive resin include thermoplastic resins, particularly hydrophilic resins and water-soluble resins, which are softened by hot water (for example, 80 to 120°C, particularly about 95 to 100°C) and can be self-adhesive or adhere to other fibers. Examples of such resins include cellulose-based resins (C1-3 alkyl cellulose ethers such as methyl cellulose, hydroxy C1-3 alkyl cellulose ethers such as hydroxymethyl cellulose, carboxy C1-3 alkyl cellulose ethers such as carboxymethyl cellulose, or salts thereof), polyalkylene glycol resins (poly C2-4 alkylene oxides such as polyethylene oxide and polypropylene oxide), polyvinyl-based resins [polyvinylpyrrolidone, polyvinyl ether, vinyl alcohol-based polymers (vinyl alcohol-based polymers containing α-C2-10 olefin units such as ethylene and propylene, particularly ethylene-vinyl alcohol-based copolymers), polyvinyl acetal resins, and the like. ol, etc.], acrylic copolymers and their salts [(meth)acrylic acid and its salts, copolymers containing units composed of acrylic monomers such as (meth)acrylamide, especially (meth)acrylic copolymers containing (meth)acrylamide units, etc.], modified vinyl copolymers (copolymers of vinyl monomers such as isobutylene, styrene, ethylene, vinyl ether, etc. and unsaturated carboxylic acids or their anhydrides such as maleic anhydride, or their salts, etc.), polymers into which hydrophilic substituents have been introduced (polyesters, polyamides, polystyrenes or their salts into which sulfo groups, carboxy groups, hydroxy groups, etc. have been introduced), aliphatic polyester resins [polylactic acid resins (e.g. polylactic acid), etc.], etc. Furthermore, among polyolefin resins, polyester resins, polyamide resins, polyurethane resins, thermoplastic elastomers or rubbers (styrene elastomers, etc.), resins that can be softened by hot water or high-temperature steam to exhibit adhesive function can also be used as moist heat adhesive resins.
[0022] The heat-and-moisture adhesive resins may be used alone or in combination of two or more kinds.
[0023] As the heat-and-moisture adhesive resin, vinyl alcohol-based polymers such as ethylene-vinyl alcohol copolymers, polylactic acid-based resins such as polylactic acid, and (meth)acrylic copolymers containing (meth)acrylamide units are preferred, vinyl alcohol-based polymers containing α-C2-10 olefin units such as ethylene and propylene are more preferred, and ethylene-vinyl alcohol-based copolymers are even more preferred.
[0024] The ethylene-vinyl alcohol copolymer can be obtained by saponifying an ethylene-vinyl ester copolymer.
[0025] Examples of the vinyl ester monomer used in the production of the ethylene-vinyl ester copolymer include vinyl formate, vinyl acetate, vinyl propionate, vinyl butyrate, vinyl isobutyrate, vinyl pivalate, vinyl versatate, vinyl caproate, vinyl caprylate, vinyl laurate, vinyl palmitate, vinyl stearate, vinyl oleate, vinyl benzoate, etc. Among these, vinyl acetate is most preferred from the viewpoint of cost.
[0026] The content (copolymerization ratio) of ethylene units in the ethylene-vinyl alcohol copolymer is, for example, about 10 to 60 mol%, preferably 20 to 55 mol%, and more preferably about 30 to 50 mol%. When the ethylene units are in this range, a unique property is obtained in which the ethylene-vinyl alcohol copolymer has wet heat adhesiveness but does not dissolve in hot water. If the ratio of ethylene units is too small, the ethylene-vinyl alcohol copolymer easily swells or gels with low-temperature steam (water), and the shape is easily changed by being wet with water only once. On the other hand, if the ratio of ethylene units is too large, the hygroscopicity decreases and fiber adhesion due to wet heat is difficult to be expressed, making it difficult to manufacture a molded body having practical strength. When the ratio of ethylene units is particularly in the range of 30 to 50 mol%, the resin of the fiber softens and adhesive points between the fibers are easily formed, so that the molded body has particularly excellent processability into a sheet or plate-like structure.
[0027] The degree of saponification of the vinyl alcohol unit in the ethylene-vinyl alcohol copolymer is, for example, about 90 to 99.99 mol%, preferably 95 to 99.98 mol%, and more preferably about 96 to 99.97 mol%. If the degree of saponification is too small, the thermal stability decreases, and the stability decreases due to thermal decomposition or gelation. On the other hand, if the degree of saponification is too large, it becomes difficult to manufacture the fiber itself. Here, the degree of saponification of the vinyl alcohol unit refers to the degree to which an alkoxycarbonyl group (also known as an ester group, RO-CO-) in the vinyl alcohol unit is hydrolyzed and replaced with a hydroxyl group, and the percentage of the hydroxyl group relative to the total number of carboxyl groups and hydroxyl groups is expressed as the degree of saponification. The degree of saponification is measured by titration with sodium hydroxide.
[0028] The viscosity average degree of polymerization of the ethylene-vinyl alcohol copolymer can be selected as necessary, but is, for example, about 200 to 2500, preferably 300 to 2000, and more preferably 400 to 1500. When the degree of polymerization is within this range, the balance between the spinnability and adhesiveness of the obtained fiber is excellent. The viscosity average degree of polymerization (P) is calculated from the viscosity (η) of the ethylene-vinyl alcohol copolymer using the following formula. logP=1.613 log{{η}×10 4 ) / 7.15}
[0029] From the viewpoint of spinning, the melt index (MI) of the ethylene-vinyl alcohol copolymer is important. MI indicates the degree of fluidity of a molten thermoplastic resin, and is a typical index for quality control of thermoplastic resins. Measurement of MI is performed in accordance with JIS K7210. The MI of the ethylene-vinyl alcohol copolymer can be selected as necessary. From the viewpoint of the balance between the spinnability and adhesiveness of the obtained fiber, the MI of the ethylene-vinyl alcohol copolymer measured under conditions of a temperature of 190°C and a load of 2160 g is preferably 1.0 to 10 g / 10 min, more preferably 1.3 to 7.0 g / 10 min, and even more preferably 1.5 to 6.6 g / 10 min.
[0030] The cross-sectional shape (cross-sectional shape perpendicular to the length direction of the fiber) of the fiber containing an ethylene-vinyl alcohol-based copolymer (hereinafter sometimes referred to as the fiber of the present invention) may be a typical solid cross-sectional shape such as a round cross-section or an irregular cross-section [flat, elliptical, polygonal, 3-14 lobes, T-shaped, H-shaped, V-shaped, dog-bone (I-shaped), etc.], or may be a hollow cross-sectional shape.
[0031] The fiber of the present invention may be a composite fiber composed of a plurality of resins. The composite fiber may have an ethylene-vinyl alcohol copolymer on at least a portion of the fiber surface, but from the viewpoint of adhesiveness, it is preferable that the ethylene-vinyl alcohol copolymer occupies at least a portion of the surface continuously in the length direction.
[0032] Examples of the cross-sectional structure of the composite fiber in which the ethylene-vinyl alcohol-based copolymer occupies the surface include a core-sheath type, an island-in-the-sea type, a side-by-side type or a multi-layered type, a radially-laminate type, a random composite type, etc. Among these cross-sectional structures, a core-sheath type structure in which the ethylene-vinyl alcohol-based copolymer occupies the entire surface continuously in the length direction (i.e., a core-sheath type structure in which the sheath portion is composed of the ethylene-vinyl alcohol-based copolymer) is preferred from the viewpoint of high adhesiveness.
[0033] In the case of composite fibers, two or more types of heat-sensitive adhesive resins under moisture may be combined, or a heat-sensitive adhesive resin under moisture and a non-heat-sensitive adhesive resin under moisture may be combined. In this specification, the term "non-heat-sensitive adhesive resin under moisture" refers to a resin that does not exhibit adhesive function under high-temperature steam or hot water.
[0034] Examples of non-humidity heat adhesive resins include water-insoluble or hydrophobic resins, specifically polyolefin resins, (meth)acrylic resins, vinyl chloride resins, styrene resins, polyester resins, polyamide resins, polycarbonate resins, polyurethane resins, and thermoplastic elastomers. These non-humidity heat adhesive resins can be used alone or in combination of two or more. Among these non-humidity heat adhesive resins, from the viewpoint of heat resistance and dimensional stability, resins (e.g., polypropylene resins, polyester resins, and polyamide resins) whose melting points are higher than the melting points of the moist heat adhesive resins (e.g., ethylene-vinyl alcohol copolymers) are preferred, and polyester resins and polyamide resins are more preferred from the viewpoint of excellent balance between heat resistance and fiber formability.
[0035] As the polyester resin, aromatic polyester resins such as polyC2-4 alkylene arylate resins [polyethylene terephthalate resins such as polyethylene terephthalate (PET), polytrimethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, etc.] are preferred, and polyethylene terephthalate resins are more preferred. In addition to ethylene terephthalate units, polyethylene terephthalate resins may contain units composed of other dicarboxylic acids [e.g., isophthalic acid, naphthalene-2,6-dicarboxylic acid, phthalic acid, 4,4'-diphenylcarboxylic acid, bis(carboxyphenyl)ethane, 5-sodium sulfoisophthalic acid, etc.] or diols (e.g., diethylene glycol, 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, neopentyl glycol, cyclohexane-1,4-dimethanol, polyethylene glycol, polytetramethylene glycol, etc.) at a ratio of about 20 mol% or less.
[0036] Preferred polyamide resins include aliphatic polyamides such as polyamide 6, polyamide 66, polyamide 610, polyamide 10, polyamide 12, polyamide 6-12, and copolymers thereof, and semi-aromatic polyamides synthesized from aromatic dicarboxylic acids and aliphatic diamines. These polyamide resins may also contain units other than amide units.
[0037] In the case of a composite fiber composed of an ethylene-vinyl alcohol copolymer and a non-thermal adhesive resin (fiber-forming polymer), the ratio (mass ratio) of the two can be appropriately selected depending on the structure (for example, core-sheath type structure). The mass ratio of the ethylene-vinyl alcohol copolymer / non-thermal adhesive resin under moisture is, for example, about 90 / 10 to 10 / 90, preferably 80 / 20 to 15 / 85, and more preferably about 60 / 40 to 20 / 80. If the ratio of the ethylene-vinyl alcohol copolymer is too high, it is difficult to ensure the strength of the fiber, and if the ratio of the ethylene-vinyl alcohol copolymer is too low, it is difficult to make the ethylene-vinyl alcohol copolymer exist continuously in the length direction of the fiber surface, and the adhesiveness is reduced. This tendency is also the case when the ethylene-vinyl alcohol copolymer is coated on the surface of a non-thermal adhesive fiber under moisture.
[0038] Preferred examples of the composite fiber include composite fibers formed from an ethylene-vinyl alcohol copolymer and a polyester resin, and composite fibers formed from an ethylene-vinyl alcohol copolymer and a polyamide resin, and more preferably composite fibers formed from an ethylene-vinyl alcohol copolymer and a polyester resin.
[0039] Examples of the fiber of the present invention that is a core-sheath type composite fiber include a core-sheath type composite fiber formed of a sheath composed of an ethylene-vinyl alcohol-based copolymer and a core composed of a non-moisture heat-adhesive resin, preferably a core-sheath type composite fiber formed of a sheath composed of an ethylene-vinyl alcohol-based copolymer and a core composed of a polyester-based resin, and a core-sheath type composite fiber formed of a sheath composed of an ethylene-vinyl alcohol-based copolymer and a core composed of a polyamide-based resin, and more preferably a core-sheath type composite fiber formed of a sheath composed of an ethylene-vinyl alcohol-based copolymer and a core composed of a polyester-based resin.
[0040] The average fineness of the present fiber is, for example, 0.01 to 100 dtex, preferably 0.1 to 50 dtex, more preferably 0.5 to 30 dtex, and particularly preferably about 1 to 10 dtex. When the average fineness is within this range, the balance between the strength of the fiber and the expression of adhesiveness is excellent. The average fineness is measured by the method of JIS L 1015.
[0041] The average fiber length of the present fiber is, for example, about 10 to 100 mm, preferably about 20 to 80 mm, more preferably about 25 to 75 mm, and particularly preferably about 35 to 55 mm. When the average fiber length is within this range, the fibers are sufficiently entangled, and the mechanical strength of the molded article is improved. The average fiber length is measured by the method of JIS L 1015.
[0042] The crimp percentage of the fiber is, for example, 1 to 50%, preferably 3 to 40%, more preferably 5 to 30%, and particularly preferably about 10 to 20%. The number of crimps is, for example, 1 to 100 per inch, preferably 5 to 50 per inch, and more preferably about 10 to 30 per inch. The crimp percentage and the number of crimps are measured by the method of JIS L 1015.
[0043] The above-mentioned "molded article having a nonwoven fiber structure and made of fibers containing an ethylene-butene-based copolymer" may further contain a non-thermal adhesive fiber. In the present specification, the term "non-thermal adhesive fiber under moisture" refers to a fiber that cannot exhibit adhesive function by either high-temperature steam or hot water.
[0044] Examples of non-heat-adhesive fibers that can be bonded under heat and moisture include polyester fibers (polyethylene terephthalate fibers, polytrimethylene terephthalate fibers, polybutylene terephthalate fibers, polyethylene naphthalate fibers, and other aromatic polyester fibers), polyamide fibers (aliphatic polyamide fibers such as polyamide 6, polyamide 66, polyamide 11, polyamide 12, polyamide 610, and polyamide 612, semi-aromatic polyamide fibers, and aromatic polyamide fibers such as polyphenylene isophthalamide, polyhexamethylene terephthalamide, and poly-p-phenylene terephthalamide), and polyolefin fibers (polyethylene, polypropylene, and other polyamide fibers). C2-4 olefin fibers, etc.), acrylic fibers (acrylonitrile fibers having acrylonitrile units such as acrylonitrile-vinyl chloride copolymers, etc.), polyvinyl fibers (polyvinyl acetal fibers, etc.), polyvinyl chloride fibers (polyvinyl chloride, vinyl chloride-vinyl acetate copolymer, vinyl chloride-acrylonitrile copolymer fibers, etc.), polyvinylidene chloride fibers (vinylidene chloride-vinyl chloride copolymer fibers, vinylidene chloride-vinyl acetate copolymer fibers, etc.), polyparaphenylene benzobisoxazole fibers, polyphenylene sulfide fibers, cellulose fibers (for example, rayon fibers, acetate fibers, etc.), etc. These non-moisture heat adhesive fibers can be used alone or in combination of two or more.
[0045] The average fineness and average fiber length of the non-thermal adhesive fiber under moisture are similar to those of the thermal adhesive fiber under moisture.
[0046] The ratio of the fiber of the present invention to the non-thermal adhesive fiber under moisture contained in the above molded product (mass ratio of the fiber of the present invention / non-thermal adhesive fiber under moisture) is, for example, 20 / 80 to 100 / 0, preferably 30 / 70 to 100 / 0. When a hard molded product is produced, it is preferable that the ratio of the fiber of the present invention is high, and the mass ratio of the fiber of the present invention / non-thermal adhesive fiber under moisture is more preferably about 80 / 20 to 100 / 0, even more preferably 90 / 10 to 100 / 0, and particularly preferably about 95 / 5 to 100 / 0. When the ratio of the fiber of the present invention is within this range, a molded product that can ensure high surface hardness and bending behavior can be obtained. When a molded product is produced using the characteristics of the non-thermal adhesive fiber under moisture, the mass ratio of the fiber of the present invention / non-thermal adhesive fiber under moisture is more preferably about 20 / 80 to 99 / 1, even more preferably 30 / 70 to 90 / 10, and particularly preferably about 40 / 60 to 80 / 20.
[0047] The fiber adhesion rate of the molded article is preferably 10 to 85%, more preferably 10 to 70%, further preferably 10 to 60%, and particularly preferably about 10 to 35%. In this specification, the term "fiber adhesion rate" refers to the ratio of the number of fibers in which two or more fibers are bonded to the total number of fibers in the cross section of the molded article having a nonwoven fiber structure (i.e., fiber adhesion rate = 100 x the number of fibers in which two or more fibers are bonded in the cross section of the molded article / the total number of fibers in the cross section of the molded article). Therefore, a low fiber adhesion rate means that the ratio of multiple fibers bonded together (the ratio of fibers bonded together) is low.
[0048] The fibers constituting the nonwoven fiber structure of the above molded article are bonded at their contact points, and in order to develop a large bending stress with as few contact points as possible, it is preferable that these bond points are uniformly distributed along the thickness direction from the surface of the molded article to the inside (center) and back surface. If the bond points are concentrated on the surface or inside, not only will it be difficult to ensure sufficient bending stress, but the shape stability will decrease in areas with fewer bond points.
[0049] The molded article is formed from the fiber of the present invention, and therefore has excellent shape stability and is easy to handle in cell culture. The molded article can maintain the voids necessary for cell adhesion and proliferation throughout the culture period, and therefore has a high ability to maintain the morphology of cells in cell culture. Therefore, by using the molded article as a culture carrier, it becomes possible to immobilize cells, particularly adherent cells, and to culture the adherent cells in three dimensions.
[0050] In addition, the molded article has a density of, for example, 0.02 to 0.7 g / cm from the viewpoints of medium components (nutrient supply) for maintaining cells in cell culture, permeability to oxygen and the like, and removal of waste products. 3 , preferably 0.025 to 0.3 g / cm 3 , and more preferably 0.03 to 0.15 g / cm 3 , and more preferably 0.075 to 0.125 g / cm 3 By adjusting the apparent density to the above range, it becomes possible to continue cell proliferation for a long period of time. Here, the "apparent density" is a value obtained by dividing the mass of a molded body having a nonwoven fiber structure containing voids by the volume of the molded body. This apparent density can also be obtained by measuring the basis weight (i.e., mass per unit area) and thickness of the molded body and dividing the basis weight by the thickness.
[0051] The molded article is substantially composed of the fiber of the present invention without being impregnated with resin. Furthermore, the nonwoven fiber structure is formed by bonding the fiber of the present invention. The molded article has a sufficiently wide cell adhesion surface and excellent shape stability when performing three-dimensional culture of adherent cells, for example. Therefore, by using the molded article as a cell culture carrier in a bioreactor or the like, efficient cell proliferation is possible.
[0052] The shape of the molded body is not particularly limited, and may be, for example, a sphere, a plate, a rod, a square, an ellipse, a disk, a cylinder, a columnar shape, or the like. Among these shapes, a sphere or a disk shape is preferable. When the molded body is used as a cell culture carrier in a bioreactor, a sphere is preferable. In particular, when used in a fluidized bioreactor, the fluidity of a spherical carrier is superior to that of carriers of other shapes. When used in a fixed-bed bioreactor, a spherical carrier is easy to fill, has small contact points between carriers, and is less likely to aggregate, making it easy to handle.
[0053] When the molded body is disc-shaped, its size is not particularly limited, and can be appropriately selected from the viewpoint of ease of handling, for example, referring to the size of a culture plate that is usually distributed. On the other hand, when the molded body is spherical, its average particle size is preferably 1 mm or more, more preferably 2 mm or more, and even more preferably 3 mm or more, from the viewpoint of facilitating separation and recovery of the carrier, and is preferably 20 mm or less, more preferably 10 mm or less, and even more preferably 6 mm or less, from the viewpoint of increasing the cell culture surface area per unit volume. The average particle size is obtained by measuring the maximum diameter of 10 randomly selected cell culture carriers using a vernier caliper and averaging them.
[0054] The molded body has a nonwoven fiber structure in which the fibers are moderately bonded, and therefore has a high bending stress even though it is lightweight and low density. The molded body has breathability and heat insulation, high hardness, and excellent folding resistance and toughness. That is, the molded body is molded into a plate shape and is unlikely to undergo local deformation even when a load is applied to the surface. It absorbs the stress by curving and deforming in response to the applied stress, so it has high impact resistance and does not easily break or break even when a strong impact is applied. Furthermore, the molded body can be substantially composed of fibers only, and does not require the addition of chemical binders or special agents, so it is inactive to cells without using any components that generate harmful components (such as volatile organic compounds such as formaldehyde).
[0055] Components other than the constituent fibers attached to the molded body may be removed by washing or the like. Examples of such components include oils. Oils are used in the general manufacturing method of nonwoven fiber structures to suppress friction between fibers in the process of entangling the fibers. The removal method is not particularly limited, but for example, the molded body may be washed using a liquid component containing water or an organic solvent, an acid / alkali component, a surfactant, or the like. The washing method is also not particularly limited, but the molded body may be immersed in the liquid component and washed. In the case of continuous washing, the molded body may be washed by passing the liquid component through the inside of the molded body while being placed on a mesh conveyor and conveyed. This washing may be performed multiple times. The molded body may be washed in stages with different liquid components. Finally, the molded body may be washed one or more times with water so that the washing components do not remain in the molded body. After washing, the liquid components may be removed by suction or compression, etc., and the liquid remaining in the molded body may be evaporated and dried by hot air or the like.
[0056] When the molded body is used for long-term cell culture, a difference in cell density occurs between the center and the outer edge of the molded body as cell growth continues for a long period of time. In order to avoid such uneven cell growth, one or more through holes may be provided in the molded body. By providing through holes, nutrition is efficiently supplied to the inside (center) of the molded body and waste products are efficiently removed, and cell growth in the molded body becomes uniform. Cell growth is also observed in the through holes. The size and number of through holes provided in the molded body may be appropriately determined depending on the size of the molded body and are not particularly limited. Depending on the size of the molded body, for example, 1 to 4 through holes, preferably 1 or 2 through holes, each having a size of about 0.5 mm to 2 mm, preferably about 0.7 μm to 1.5 mm, may be provided.
[0057] The molded article is produced by forming a nonwoven fiber structure using the fiber of the present invention. Any method known in the art may be used for such production. For example, when the fiber of the present invention is a wet heat adhesive fiber, it can be produced by the following method. First, the fiber containing the fiber of the present invention is made into a web. As a method for forming the web, a conventional method, for example, a direct method such as a spunbond method or a meltblowing method, a carding method using staple fibers, or a dry method such as an airlaying method, can be used. Among these methods, the carding method using staple fibers is particularly widely used. Examples of webs obtained using staple fibers include random webs, semi-random webs, parallel webs, and cross-lap webs. Among these webs, when the proportion of bundle-shaped fusible fibers is to be increased, semi-random webs and parallel webs are preferred. Next, the obtained fiber web is sent to the next process by a mesh conveyor, and then exposed to a flow of superheated steam or high-temperature steam (high-pressure steam), to obtain a molded article having a nonwoven fiber structure. That is, when the fiber web transported by the mesh conveyor passes through a high-temperature steam flow ejected from the nozzle of the steam ejector, the fibers are bonded three-dimensionally by the sprayed high-temperature steam.
[0058] The belt conveyor used is not particularly limited as long as it can compress the fiber web used in processing to the desired density while treating it with high-temperature steam, and an endless mesh conveyor is preferably used. A general single mesh conveyor may be used, or two mesh conveyors may be combined as necessary to transport the web sandwiched between the two mesh conveyors. By transporting the web in this manner, it is possible to suppress deformation of the shape of the transported web due to external forces such as water used in the processing, high-temperature steam, and vibration of the mesh conveyor when processing the web. In addition, it is also possible to control the density and thickness of the molded body having a nonwoven fiber structure after processing by adjusting the interval of the belt.
[0059] When two mesh conveyors are combined, the steam injection device for supplying steam to the web is installed in one of the mesh conveyors and supplies steam to the web through the mesh structure of the conveyor. A suction box may be installed in the mesh conveyor on the opposite side. The suction box can suck and discharge excess steam that has passed through the web. In order to steam both the front and back sides of the web at once, a suction box may be installed downstream of the mesh conveyor on the side on which the steam injection device is installed, and a steam injection device may be installed in the mesh conveyor on the opposite side to which the suction box is installed. In the case where there is no downstream steam injection device or suction box, the front and back sides of the fiber web can be steam-treated by turning over the front and back sides of the fiber web once treated and passing it through the treatment device again.
[0060] The shape of the mesh conveyor is not particularly limited as long as it does not interfere with the transportation of the web or the high-temperature steam treatment. However, when the high-temperature steam treatment is performed, the surface shape of the belt may be transferred to the surface of the fiber web depending on the conditions, so it is preferable to select the shape appropriately according to the application. In particular, when it is desired to obtain a molded product with a flat surface, a fine mesh net may be used. Note that the upper limit is about 90 mesh, and nets with meshes finer than this have low breathability and make it difficult for water vapor to pass through. From the viewpoint of heat resistance against steam treatment, the material of the mesh conveyor is preferably metal, heat-resistant polyester resin, polyphenylene sulfide resin, polyarylate resin (fully aromatic polyester resin), aromatic polyamide resin, or other heat-resistant resin.
[0061] Since the high-temperature steam injected from the steam injection device is an airflow, unlike the hydroentanglement process or needle punch process, it penetrates into the web without significantly moving the fibers in the web, which is the object to be treated. It is considered that the penetration action of the water vapor flow into the web and the moist heat action cause the water vapor flow to efficiently cover the surface of each fiber present in the web in a moist heat state, enabling uniform thermal bonding. In addition, since this treatment is performed in an extremely short time under a high-speed airflow, the heat conduction of the water vapor to the fiber surface is sufficient, but the treatment ends before the heat conduction to the inside of the fiber is sufficient, so that the pressure and heat of the high-temperature steam do not easily cause deformation such as the entire fiber web being crushed or the thickness being lost. As a result, the moist heat bonding is completed so that the degree of adhesion on the surface and in the thickness direction is roughly uniform without causing any significant deformation of the fiber web.
[0062] Furthermore, when obtaining a molded product having high surface hardness and bending strength, it is important that the web to be treated is compressed to the desired apparent density between mesh conveyors or rollers and exposed to high-temperature steam when high-temperature steam is supplied to the web for treatment. In particular, when a relatively high-density molded product is to be obtained, the fiber web needs to be compressed with sufficient pressure when treated with high-temperature steam. Furthermore, by ensuring a suitable clearance between the mesh conveyors or rollers, it is possible to adjust the thickness and density to the desired thickness and density. In the case of a mesh conveyor, since it is difficult to compress the web all at once, it is preferable to set the tension of the mesh conveyor as high as possible and gradually narrow the clearance from the upstream of the steam treatment point. Furthermore, the molded product having the desired bending hardness, surface hardness, lightness, and air permeability is processed by adjusting the steam pressure and treatment speed.
[0063] In this case, if it is desired to increase the hardness, the back side of the mesh conveyor opposite the nozzle with the web sandwiched between them can be made of a stainless steel plate or the like to prevent water vapor from passing through, and the water vapor that passes through the web to be treated will be reflected by this plate, so that the fiber of the present invention will be firmly bonded by the heat-retaining effect of the water vapor. Conversely, if light bonding is required, a suction box can be provided to exhaust excess water vapor to the outside of the room.
[0064] The nozzle for spraying high-temperature steam may be a plate or die having predetermined orifices arranged continuously in the width direction, and may be arranged so that the orifices are arranged in the width direction of the web to be fed. There may be one or more orifice rows, and multiple rows may be arranged in parallel. Also, multiple nozzle dies each having a single orifice row may be installed in parallel.
[0065] When using a nozzle with an orifice on a plate, the thickness of the plate may be, for example, about 0.5 to 1 mm. There is no particular restriction on the diameter and pitch of the orifice as long as the desired fiber fixation is possible, but the diameter of the orifice is usually about 0.05 to 2 mm, preferably about 0.1 to 1 mm, and more preferably about 0.2 to 0.5 mm. The pitch of the orifice is usually about 0.5 to 3 mm, preferably about 1 to 2.5 mm, and more preferably about 1 to 1.5 mm. If the diameter of the orifice is too small, the processing accuracy of the nozzle is low, which makes processing difficult, and the operational problem of clogging is likely to occur. Conversely, if the diameter of the orifice is too large, the steam injection force decreases. On the other hand, if the pitch is too small, the nozzle holes become too dense, and the strength of the nozzle itself decreases. On the other hand, if the pitch is too large, there are cases where the high-temperature steam does not sufficiently hit the entire surface of the web, so the adhesion between the fibers in the web becomes uneven, and the strength of the molded body decreases.
[0066] The high-temperature steam is not particularly limited as long as it can fix the fibers as desired, and may be set according to the material and shape of the fibers used. The pressure is, for example, about 0.05 to 2 MPa, preferably 0.05 to 1.5 MPa, and more preferably about 0.1 to 1 MPa. If the steam pressure is too high, the fibers forming the web may move, causing a disturbance in the texture, or the fibers may melt too much and partially lose their fiber shape. If the pressure is too low, the amount of heat required for fusing the fibers may not be given to the web, or the steam may not penetrate the web, causing fiber fusing spots in the thickness direction, and it may be difficult to control the uniform ejection of the steam from the nozzle.
[0067] The temperature of the high-temperature steam is, for example, about 70 to 150° C., preferably about 80 to 120° C., and more preferably about 90 to 110° C. The processing speed of the web with the high-temperature steam is, for example, 200 m / min or less, preferably about 0.1 to 100 m / min, and more preferably about 1 to 50 m / min.
[0068] If necessary, it is possible to impart a predetermined uneven shape to the mesh conveyor and then transfer the uneven shape to the board product obtained. In addition, the board may be laminated with other materials to form a laminate, or may be processed into a desired shape (such as a cylindrical, rectangular prism, spherical, or ellipsoidal shape) by molding.
[0069] In this way, after the fibers of the fiber web are partially wet-heat bonded, moisture may remain in the obtained molded body, so the web may be dried as necessary. Regarding drying, it is necessary that the surface of the molded body that contacts the drying heater does not lose its fiber form due to melting of the fibers after drying, and as long as the fiber form can be maintained, a conventional method can be used. For example, large drying equipment such as a cylinder dryer or tenter used for drying nonwoven fabrics may be used, but since the remaining moisture is small and is often at a level that can be dried by a relatively mild drying means, non-contact methods such as far-infrared irradiation, microwave irradiation, and electron beam irradiation, and methods using hot air are preferred.
[0070] Furthermore, the molded article is obtained by bonding the fibers of the present invention with high-temperature steam as described above, but the fibers may be bonded by other conventional methods, such as heat-pressure fusion (such as heat embossing), mechanical compression (such as needle punching), etc. Furthermore, other conventional methods may be used to bond the obtained molded articles together.
[0071] When the fiber of the present invention is a heat-and-moisture adhesive fiber, the fiber web can also be bonded by immersing it in hot water. However, when immersing in hot water, it is difficult to control the fiber adhesion rate, and it is also difficult to obtain a molded product with a high uniformity in the fiber adhesion rate. The reasons for this are presumably that the heat-and-moisture adhesiveness differs depending on the position due to the influence of the air inevitably contained in the fiber web, the influence on the structure caused by the air being pushed out of the fiber web, the deformation of the microstructure inside the fiber caused by the take-up roller when the heat-and-moisture adhesive fiber web is taken out of the hot water, and the difference in deformation of the microstructure in the vertical direction caused by the weight of the hot water contained in the taken-out fiber web.
[0072] The molded article obtained as described above can be further processed by a known method (eg, pressing, cutting) to form it into a desired shape.
[0073] In the manufacturing method of the present invention, the molded body is used as a cell culture carrier to culture adherent cells. That is, the adherent cells are supported on the molded body and cultured. The cells may be supported by any method as long as the cells are ultimately supported on the molded body. Since the cells are adherent cells, the cells can easily adhere to the molded body by contacting the molded body and are supported on or in the molded body. For example, the adherent cells can be supported on the molded body by a method of dropping a cell suspension onto the molded body, a method of immersing the molded body in a cell suspension, or the like. The cell suspension is, for example, in a liquid such as water or a culture medium, preferably at 10 3 ~10 8 cells / ml, more preferably 10 3 ~10 6The adherent cells may be in the form of a suspension having a concentration of about 1000 cells / ml. The adherent cells are preferably supported in the gaps between the fibers of the molded body.
[0074] The adherent cells thus supported on the molded body are then cultured under stirring. For the culture, culture conditions such as a culture medium and culture temperature suitable for the cells to be cultured (i.e., the adherent cells supported on the molded body) may be selected. Examples of culture conditions include those described in "Cultured Cell Handbook: All about the Basics and Analysis of Cell Culture," edited by Toshio Kuroki and Hiroshi Kyo, Yodosha, published in July 2004.
[0075] A liquid medium is preferably used as the culture medium, and a conventional medium suitable for the adherent cells to be cultured may be used. For example, when culturing animal cells, a medium containing various components such as various essential amino acids, various vitamins, and sugars such as glucose (e.g., Dulbecco's modified Eagle's medium, etc.) may be used. The content of the components in the culture medium may be an amount suitable for culturing cells. Furthermore, the medium may be, for example, a fetal bovine serum medium, a serum-free medium, a human serum medium, etc.
[0076] Stirring may be performed, for example, using a stirrer or shaker. The stirring speed is, for example, about 30 rpm to 140 rpm, preferably about 50 rpm to 90 rpm. Stirring is performed during at least a part of the culture period, and preferably throughout the entire culture period.
[0077] In the manufacturing method of the present invention, the aggregation of adherent cells in the molded body is promoted by stirring, and cell aggregates are efficiently formed. Furthermore, the cell aggregates formed in the molded body are separated from the molded body and released into the medium by stirring. The cell aggregates thus produced can be easily collected from the medium by a method such as filtration.
[0078] The present invention will be described in more detail below using examples and comparative examples, but the present invention is not limited to the examples. EXAMPLES
[0079] Example 1: Production of cell aggregates by the production method of the present invention 1 (1) Preparation of molded body 0.1g / cm 3 A disk-shaped molded body having an apparent density of 2 mm thick and 6 mm in diameter was produced. Two through holes with a diameter of about 1 mm were provided in the molded body. The fiber in question was a core-sheath type composite staple fiber ("Sophista" manufactured by Kuraray Co., Ltd., average fineness 1.7 dtex, average fiber length 51 mm, mass ratio of ethylene-vinyl alcohol copolymer / non-humid heat adhesive resin = 50 / 50, number of crimps 22.9 / inch, crimp rate 12.2%), with a core component of polyethylene terephthalate and a sheath component of ethylene-vinyl alcohol copolymer (ethylene content 44 mol%, saponification degree 98.4 mol%, MI (temperature 190°C and load 2160 g) 5.5 g / 10 min), and the fiber was cut by a carding method to a basis weight of about 100 g / m 2 Seven sheets of this web were stacked together to obtain a total basis weight of 700 g / m 2 This carded web was transferred to a mesh conveyor equipped with a stainless steel endless net having a mesh size of 500 mm and a width of 500 mm.
[0080] The mesh conveyor is composed of a pair of conveyors, a lower conveyor and an upper conveyor, and steam injection nozzles are installed on the back side of the belts of both conveyors, so that high-temperature steam can be injected through the belts onto the passing web. Furthermore, metal rolls for adjusting the thickness of the web (hereinafter sometimes abbreviated as "web thickness adjustment rolls") are installed upstream of the nozzles. The upper conveyor has a flat upper surface (i.e., the surface through which the web passes), while the lower surface of the upper conveyor is curved along the web thickness adjustment roll, and the web thickness adjustment roll of the upper conveyor is disposed so as to form a pair with the web thickness adjustment roll of the lower conveyor. The upper conveyor can also move up and down, so that the distance between the web thickness adjustment rolls of the upper conveyor and the lower conveyor can be adjusted to a predetermined distance. Furthermore, the upstream side of the upper conveyor is inclined at an angle of 30 degrees (relative to the lower surface of the downstream side of the upper conveyor) with the web thickness adjustment roll as the base point, and the downstream part is bent so as to be arranged parallel to the lower conveyor. When the upper conveyor moves up and down, it moves while maintaining this parallel relationship. These mesh conveyors rotate at the same speed and in the same direction, and these two conveyor belts and the web thickness adjustment rolls are structured so that they can pressurize while maintaining a predetermined clearance. This operates like a so-called calendar process to adjust the web thickness before steam treatment. That is, the card web sent from the upstream side runs on the lower conveyor, but the gap with the upper conveyor gradually narrows before reaching the web thickness adjustment roll. Then, when this gap becomes narrower than the web thickness, the web is sandwiched between the upper and lower conveyor belts and runs while being gradually compressed. The web is compressed to a thickness approximately equal to the clearance of the web thickness adjustment roll, steamed at that thickness, and then runs downstream of the conveyor while maintaining the same thickness. Here, the web thickness adjustment roll was adjusted to a linear pressure of 50 kg / cm.
[0081] The carded web was then introduced into a steam injection device attached to the lower conveyor, and 0.4 MPa high-temperature steam was injected from this device so as to pass through the carded web in the thickness direction (vertically) to perform steam treatment, thereby obtaining a molded article having a nonwoven fiber structure. This steam injection device had a nozzle installed in the lower conveyor so as to blow high-temperature steam toward the web through a conveyor net, and a suction device was installed on the upper conveyor. In addition, another injection device was installed downstream of this injection device in the web traveling direction, which was a combination of a nozzle and a suction device in the reversed position, and steam treatment was performed on both the front and back sides of the web.
[0082] The water vapor injection nozzle had a hole diameter of 0.3 mm, and the nozzles were arranged in a row at 1 mm pitch along the width direction of the conveyor. The processing speed was 3 m / min, and the gap (distance) between the upper and lower conveyor belts on the nozzle side and the suction side was 10 mm. The nozzle was placed on the back side of the conveyor belt so that it was almost in contact with the belt.
[0083] The molded product thus obtained had a board-like shape, was much harder than ordinary nonwoven fabrics, and had excellent shape stability. The fiber adhesion rate of the molded product thus obtained was 26.7%. The molded product thus obtained was processed into a plate with a thickness of 2 mm, and then hollowed out into a disk with a diameter of 6 mm.
[0084] The obtained disk-shaped molded body was provided with two through holes with a diameter of about 1 mm.
[0085] (2) Cell culture using molded bodies under agitation Cells were seeded on the molded bodies prepared in (1) above. Human immortalized adipose-derived mesenchymal stem cells (Adipose Derived Stem Cells: ADSCs (ASC52telo)) were used as the cells. The cells were suspended in the medium to prepare a cell suspension of 6×10^6 cells / mL, and the cells were seeded by dropping 45 μL per molded body with a micropipette. The ADSCs seeded on the molded bodies were cultured in a spinner flask (medium volume 50 mL) at 37°C with stirring (70 rpm) for 20 days. The medium used was Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS, 50 U / mL penicillin, and 50 μg / mL streptomycin. Half of the medium was replaced twice every 7 days.
[0086] (3) Cell aggregates The formation of cell aggregates was observed by the above-mentioned (2) culture. Granular cell aggregates floating in the medium were observed. The cell aggregates were collected by filtration. The size of the obtained cell aggregates was measured by dimensional measurement in a microscopic observation photograph. As a result, cell aggregates with a diameter or major axis of about 2 mm were obtained.
[0087] Example 2: Production of cell aggregates by the production method of the present invention 2 (4) Preparation of molded body A disk-shaped molded body having no through holes was produced by the method of Example 1(1).
[0088] (5) Cell culture using molded bodies under agitation Cells were seeded on the molded bodies prepared in (4) above. Human immortalized adipose-derived mesenchymal stem cells (ADSCs) were used as the cells. The cells were suspended in the medium to prepare a cell suspension of 6×10^6 cells / mL, and the cells were seeded by dropping 45 μL per molded body with a micropipette. The ADSCs seeded on the molded bodies were cultured in a spinner flask (medium volume 50 mL) at 37°C with stirring (70 rpm) for 25 days. The medium used was Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS, 50 U / mL penicillin, and 50 μg / mL streptomycin. Half of the medium was replaced twice every 7 days.
[0089] (6) Cell aggregates The formation of cell aggregates was observed by the above-mentioned (5) culture. Granular cell aggregates floating in the medium were observed. The cell aggregates were collected by filtration. The size of the obtained cell aggregates was measured by dimensional measurement in a microscopic observation photograph. As a result, cell aggregates with a diameter or major axis of about 2 mm were obtained.
[0090] Comparative Example 1: Production of cell aggregates by cell culture without stirring Cells were seeded on the molded body prepared in Example 1 in the same manner as in Example 1. ADSCs were used as the cells. The ADSCs seeded on the molded body were cultured in a 12-well dish (1 mL of medium) at 37°C for 20 days under static conditions. The medium used was Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% FBS, 50 U / mL penicillin, and 50 μg / mL streptomycin. Half of the medium was replaced twice every 7 days. After 20 days of culture, no formation of cell aggregates was observed.
[0091] Comparative Example 2: Preparation of cell aggregates by conventional method 1 ADSCs were suspended in the medium to prepare a cell suspension of 2.5×10^5 cells / mL. The medium used was Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% FBS, 50 U / mL penicillin, and 50 μg / mL streptomycin. 1 mL of the cell suspension was placed in a 5 mL centrifuge tube and cultured at 37°C for 45 days. Half of the medium was replaced twice every 7 days. After 45 days of culture, the formation of cell aggregates was observed. The size of the obtained cell aggregates was measured in the same manner as in Example 1. As a result, the diameter or major axis was about 1.5 mm.
[0092] Comparative Example 3: Preparation of cell aggregates by conventional method 2 ADSCs were suspended in culture medium to prepare a cell suspension of 1.0×10^4 cells / mL. The culture medium used was Dulbecco's Modified Eagle Medium (DMEM) supplemented with 10% FBS, 50 U / mL penicillin, and 50 μg / mL streptomycin. 1 mL of the cell suspension was placed in a 96-well U-bottom plate and cultured at 37°C for 2 days. After culturing for 2 days, the formation of cell aggregates was observed. The size of the obtained spheroids was measured in the same manner as in Example 1. As a result, the diameter or major axis was about 500 μm.
[0093] Assessment of cell viability in cell aggregates The cell viability was evaluated in the cell aggregates obtained in Example 1 and Comparative Example 2. For the evaluation, a Live-Dead Assay was performed using a confocal laser microscope. The evaluation was performed using a Live or DeadTM (registered trademark) Cell Viability Assay Kit (manufactured by Thermo Fisher Scientific). The kit uses two types of dyes, namely, Calcein AM (for live cells) and a cell-impermeable DNA-binding dye. When non-fluorescent Calcein AM is hydrolyzed by endogenous esterase, it produces hydrophilic Calcein that tends to accumulate in the cytoplasm. The esterase activity is proportional to the number of live cells. The DNA-binding dye does not penetrate live cells with intact membranes and binds only to the DNA of dead cells. This allows Live / Dead to be evaluated with green / red.
[0094] As a result, the survival of cells inside the cell aggregate obtained in Example 1 was observed, whereas the survival of cells inside the cell aggregate obtained in Comparative Example 2 was not observed ( FIG. 1 ). This is believed to be because the molded article containing the heat-and-moisture adhesive fiber and having a nonwoven fiber structure has an appropriate hydrophilicity, which promotes the production of extracellular matrix, thereby suppressing excessive cell crowding and improving cell survival.
[0095] Assessment of cell viability in cell aggregates after freezing and thawing The cell aggregates obtained in Example 1 and the cell aggregates obtained in Comparative Example 3 were subjected to a cell viability evaluation after freezing and thawing. After rinsing the cell aggregates with PBS (phosphate buffered saline), the cell aggregates were placed in a microtube containing 1 mL of a cryopreservative CELLBANKER1 (manufactured by Xenogen Pharma Co., Ltd.), and then shaken for 30 seconds with an orbital shaker. The CELLBANKER1 in the microtube was removed, and the same amount of CELLBANKER1 was newly added. The microtube was placed in a cell freezing container Mr. Frosty (manufactured by Thermo Fisher Scientific) and frozen in a deep freezer at -90°C for 24 hours. It was then kept in liquid nitrogen for 24 hours. The microtube was removed from the liquid nitrogen and thawed in a water bath at 37°C. The cell aggregates in the microtube were removed, and a Live-Dead Assay was performed in the same manner as above.
[0096] As a result, the cell aggregates obtained in Example 1 were found to maintain internal cell survival even after freezing and thawing (Figure 2). On the other hand, the cell aggregates obtained in Comparative Example 3 were found to maintain internal cell survival (Figure 2). Therefore, the cell aggregates of the present invention were found to have improved cell survival after freezing and thawing compared to conventional cell aggregates. Normally, when cells are frozen, ice destroys the cell membrane, leading to cell death, but in the cell aggregates of the present invention, the presence of the extracellular matrix inhibits the growth of ice, reducing damage to the cells.
[0097] Identification of extracellular matrix in cell aggregates Picrosirius red staining was performed on the cell aggregates obtained in Example 1 and the cell aggregates obtained in Comparative Example 2. Staining was performed using a Picrosirius Red Staining Kit (manufactured by ScyTek Laboratories). In Picrosirius Red staining, collagen is stained red, and cytoplasm and other proteins are stained yellow. After staining, the red and yellow regions were visually identified, and the areas of the above regions were analyzed using image analysis software WinROOF (manufactured by Mitani Shoji Co., Ltd.).
[0098] As a result, in the cell aggregate obtained in Example 1, the percentage of the area stained red was 45.3%, indicating that components other than collagen accounted for approximately 50% or more of the total (FIG. 3). On the other hand, in the cell aggregate obtained in Comparative Example 2, almost 100% was stained red, indicating that collagen was the main component of the extracellular matrix (FIG. 3).
Claims
1. A cell aggregate comprising adherent cells and an extracellular matrix, the cell aggregate comprising viable cells even at a depth of 30 μm or more from the surface of the aggregate.
2. The cell aggregate described in claim 1, which contains viable cells even at a depth of 30 μm or more from the surface of the aggregate after freezing and thawing the aggregate.
3. The cell aggregate of claim 1 , which is granular with a diameter of more than 1.5 mm.
4. The cell aggregate of claim 1 , wherein less than 50% of the extracellular matrix is collagen.
5. The cell aggregate according to any one of claims 1 to 4, which is in a frozen state.
6. A method for producing a cell aggregate, comprising supporting adherent cells on a molded body having a nonwoven fiber structure and made of fibers containing an ethylene-vinyl alcohol copolymer, and culturing the cells under stirring.
7. The method according to claim 6, wherein the fiber containing the ethylene-vinyl alcohol copolymer is a heat-adhesive fiber under moisture.
8. The method according to claim 6, wherein the fiber containing the ethylene-vinyl alcohol-based copolymer is a conjugate fiber containing a non-thermal adhesive fiber under moisture.
9. The manufacturing method according to claim 8, wherein the composite fiber is a core-sheath type composite fiber including a sheath portion made of an ethylene-vinyl alcohol-based copolymer and a core portion made of a polyester-based resin.
10. 0.02~0.7g / cm 3 The method according to any one of claims 6 to 9, comprising supporting adherent cells on the molded body having an apparent density of 0.01 to 0.1 mm and culturing the cells under stirring at 30 to 140 rpm.
Citation Information
Patent Citations
Three dimensional cell culture compositions and methods of use
US20140051168A1
Freezing method for aggregates of pluripotent stem cell-derived myocardial cells
WO2017159862A1
Frozen transplant and method for producing frozen transplant
JP7105487B2